Odpowiedzi

2010-04-10T17:30:42+02:00
(1-3x) (-2y-3)=-2y-3+6xy+9x=6xy+9x-2y-3

(x-2) (2y+6)=2xy+6x-4y-12

(2x+3y) (x-4y)=2x²-8xy+3xy-12y²=2x²-12y²-5xy

(3a-2b) (-3b+2a) = -3ab+6a²+6b²-4ab=6a²+6b²-7ab
Najlepsza Odpowiedź!
2010-04-10T17:31:30+02:00
A) (1-3x) (-2y-3)= -2y-3+6xy+9x
b) (x-2) (2y+6)=2xy+6x-4y-12
c) (2x+3y) (x-4y)=2x²+8xy+3xy+12y²=2x²+11xy+12y²
d) (3a-2b) (-3b+2a)=-9ab+6a²+6b²-4ab=6a²+6b²-13ab
2010-04-10T17:31:41+02:00
A) (1-3x) (-2y-3) = - 2y - 3 + 6xy + 6x
b) (x-2) (2y+6) = 2xy + 6x - 4y + 12
c) (2x+3y) (x-4y) = 2x² - 5xy - 12y²
d) (3a-2b) (-3b+2a) = -13ab + 6a² + 6b²